Solar wind interaction with the Earth's magnetosphere: the role of reconnection in the presence of a large scale sheared flow - F. Califano; M. Faganello; F. Pegoraro; F. Valentini (Nonlinear Processes in Geophysics, 2009)
The Earth's magnetosphere and solar wind environment is a laboratory of excellence for the study of the physics of collisionless magnetic reconnection. At low latitude magnetopause, magnetic reconnection develops as a secondary instability due to the stretching of magnetic field lines advected by large scale Kelvin-Helmholtz vortices. In particular, reconnection takes place in the sheared magnetic layer that forms between adjacent vortices during vortex pairing. The process generates magnetic islands with typical size of the order of the ion inertial length, much smaller than the MHD scale of the vortices and much larger than the electron inertial length. The process of reconnection and island formation sets up spontaneously, without any need for special boundary conditions or initial conditions, and independently of the initial in-plane magnetic field topology, whether homogeneous or sheared.